MICROSCOPICAL OBSERVATION OF KIDNEY FOR AMELIORATIVE EFFECTS OF VITAMIN - E & C IN STREPTOZOTOCIN-INDUCED DIABETIC RATS: Life Science-Biochemistry - GANESH E; CHOWDHURY A; MALARVANI T; VARDHAN N, ASHOK (International Journal of Life Science and Pharma Research, 2012)
Oxidative stress has been suggested as a contributory factor in development and complication of diabetes. Diabetic nephropathy is a serious complication of diabetes mellitus. Oxidative stress has been suggested to play a key role in the pathogenesis of diabetic nephropathy. The aim of the study is to evaluate the effect of Vitamins – E & C (VEC) roles in the antioxidant defense system. It is likely that both Vitamins act in a synergistic manner, with Vitamin E primarily being oxidized to the tocopheroxyl radical and then reduced back to tocopherol by Vitamin C. The purpose of this study was to determine the effects of supplementation of Vitamins – E & C (VEC) on diabetic rat kidney. Adult albino rats were used in the study. The animals were divided into three groups. Group-A: Control group (C); Group-B: Diabetic group (D), streptozotocin (60mg/kg body weight for 3 consecutive days) was administered group; Group-C: Diabetes+Vitamins–E&C (D + VEC) group, received a diet containing a combination of ascorbic acid and di-tocopheryl acetate per kg of feed. Rats were sacrificed on day 21 and renal tissues were taken for Microscopical examination. When compared with the control group, congestion of the glomerular capillaries, increased mesangial cells and distinct mesangium, shortened podocyte processes and disappearance of filtration slit pore of diabetic rat kidney were observed. In the group treated with VEC, glomerular changes were less distinct than the diabetic group. Lengths of the pedicles were similar to the control group. In conclusion, VEC reduced the changes in the glomerular structures due to diabetes.